Comparative Phenotypic and Transcriptomic Analysis Reveals Key Responses of Upland Cotton to Salinity Stress During Postgermination - Zhang, Jingxia; Zhang, Pei; Huo, Xuehan; Gao, Yang; Chen, Yu; Song, Zhangqiang; Wang, Furong; Zhang, Jun (Frontiers in Plant Science, 2021)
To understand the molecular mechanisms of salinity tolerance during seed germination and post-germination stages, this study characterized phenotypic and transcriptome responses of two cotton cultivars during salinity stress. The two cultivars were salt-tolerant (ST) LMY37 and salt-sensitive (SS) ZM12, with the former exhibiting higher germination rate, growth, and primary-root fresh weight under salinity stress. Transcriptomic comparison revealed that up-regulation of differentially expressed genes (DEGs) was the main characteristic of transcriptional regulation in ST, while SS DEGs were mainly down-regulated. GO and KEGG analyses uncovered both common and specific responses in ST and SS. Common processes, such as reactive oxygen species (ROS) metabolism and cell wall biosynthesis, may be general responses to salinity in cotton. In contrast, DEGs involved in MAPK-signaling pathway activated by ROS, carotenoid biosynthesis pathway and cysteine and methionine metabolism pathway [producing the precursors of stress hormone abscisic acid (ABA) and ethylene (ET), respectively] as well as stress tolerance related transcription factor genes, showed significant expression differences between ST and SS. These differences might be the molecular basis leading to contrasting salinity tolerance. Silencing of GhERF12, an ethylene response factor gene, caused higher salinity sensitivity and increased ROS accumulation after salinity stress. In addition, peroxidase (POD) and superoxide dismutase (SOD) activity obviously declined after silencing GhERF12. These results suggest that GhERF12 is involved in salinity tolerance during early development. This study provides a novel and comprehensive perspective to understand key mechanisms of salinity tolerance and explores candidate genes that may be useful in developing stress-tolerant crops through biotechnology.